Monitoring with Closed-Loop Strategy to Transform the Role of Internal Audit Units in Hospitals - Sinta Kurniawati; Arlina Dewi (LPPM Institut Bisnis dan Informatika Kesatuan, 2026)
The paradigm shift in internal auditing requires internal audit units to move beyond administrative supervision and become agents of organizational change, yet this role remains constrained in many regional hospitals by weak follow-up, auditee resistance, and limited monitoring systems. This study analyzes how monitoring strategies transform the internal audit unit’s role as supervisor, consultant, and catalyst in hospital governance. A qualitative study was conducted at Daha Husada Regional General Hospital, a provincial public hospital with BLUD status. Data were collected through in-depth interviews with ten informants, observation, and document analysis, then examined through open, axial, and thematic coding using the Input-Process-Output framework. The findings show that closed-loop monitoring, involving appointment of a person in charge, time targets, evidence verification, and periodic reporting, improves implementation of audit recommendations and changes perceptions of the internal audit units from a control symbol to a strategic partner. Monitoring also functions as organizational learning that strengthens compliance culture and cross-unit collaboration. Key barriers include limited human resources, inconsistent management support, and the absence of an integrated monitoring system. Thus, monitoring operates as a governance intervention that repositions internal audit toward collaborative assurance and learning in public hospitals.